PELAKSANAAN KEGIATAN EKSTRAKURIKULER MARCHING BAND GITA ABDI PRAJA DI IPDN KAMPUS SUMATERA BARAT - Rangga Agusta; Erfan Lubis; Yos Sudarman (SENDRATASIK UNP, 2016)
This research is aimed at finding out and describing the implementation of the extracurricular activity of the Marching Band Gita Abdi Praja in IPDN Campus, Baso West Sumatra. The extracurricular activity has been carried on since mid-2013.   This is a descriptive qualitative research. The object of study is the Madya Praja students of IPDN, Campus Baso West Sumatra who were involved in the activities of the marching band. The instrument of the research is the researcher herself, who played the role as the observer and participant-an insider who directly took part in investigating the research objects. Supporting data consists of the result of documentation obtained from observation, interviews list and pictures.   The result of study shows that the IPDN Campus conducted the estracurricular activities by first preparing the recruitment process of the Madya Praja students and then selecting them based on the availability of the Marching band equipments and the students ability. Before the Marching Band practices were conducted, the trainer grouped the students into two groups those who would play the percussion instruments (Snare, tenor, cymbal, quintom and bass drum) and the melody instruments (Bellyra, Marching Bell, Brass Instruments.) Next the two group were united to play the instruments collaboratively. The result of evaluation shows that the Praja kept on making progress every time they gathered for practice. This was the result of the good work of both the advisor and trainer who planed and implemented the Marching Band activities in accordance with the procedures.